DETERMINANT CORPORATE GOVERNANCE AND OWNERSHIP STRUCTURE IN INCREASING THE COMPANY'S FINANCIAL PERFORMANCE - Suhendar Suhendar; Wildoms Sahusilawane; Teguh Setiawan Wibowo; Irwan Moridu; Inova Fitri Siregar (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research is motivated by the importance of the company's financial performance as a decision-making material for stakeholders. This study aims to identify and analyze the Determinants of Corporate Governance and Ownership Structure in Improving Corporate Financial Performance. This research method is descriptive with a quantitative approach. The population in this study are all property companies listed on the IDX for 2018-2021. The sample of this research is 15 companies according to the criteria. Research data was obtained from the annual report for the 2018-2021 period. The analytical method used is panel data regression analysis with Eviews for Windows version 9.0 software. The results showed that 1) Corporate governance has a positive and significant effect on the company's financial performance, 2) Ownership structure has a positive and significant effect on the company's financial performance, and 3) Corporate governance and ownership structure have a positive and significant effect on the company's financial performance. The findings of this study indicate that if a company wants to improve its financial performance, the company must improve its corporate governance and ownership structure.